Pandemic preparedness and response: a survey among experts from high- and low-middle-income countries about the “100 Days Mission” - Pencelli, Vanessa; Clemens, Ralf; Bica, Mihai Alexandru; Clemens, Sue Ann Costa (Frontiers in Public Health, 2025)
BackgroundThe “100 Days Mission” (100DM), designed by the Coalition for Epidemic Preparedness Innovations (CEPI), represents an ambitious new concept in vaccine development for effective pandemic preparedness, rapid response, and the reduction of health inequalities. We aimed to identify potential obstacles to the success of the 100DM by conducting a survey among experts in vaccinology and public health from both high-income countries (HICs) and low- and middle-income countries (LMICs).Materials and methodsA descriptive cross-sectional study was conducted, using a semi-structured online survey distributed to 116 experts from both LMICs and HICs. The data collected were analyzed quantitatively and qualitatively, highlighting the differences in responses between the LMICs and HICs respondents.ResultsThe overall response rate was 73.2% (85/116), with 74% (57/77) of the respondents from HICs and 69.2% (27/39) from LMICs. The LMIC respondents (14/27, 51.9%) were more confident in the success of the 100DM than the HIC respondents (15/57, 26.3%). Additionally, LMIC respondents believed more strongly in the potential impact to overcome inequalities (15/27, 55.6% vs. 19/57, 33.3%). Almost all experts from both LMICs and HICs considered political will and governance, and sufficient sustainable funding as the most important prerequisites for the success of the 100DM, followed by the need for trustful collaborations between HICs and LMICs, effective public–private partnership, and continuous training and capability building. The 100DM should prioritize the establishment of vaccine candidate libraries, enhancement and sustainability of surveillance capabilities, and creation of laboratory and clinical trial site networks.ConclusionThis is the first prospective survey evaluating the feasibility of 100DM, involving external stakeholders from both HICs and LMICs. Experts from LMICs are more confident in the success of the 100DM than those from HICs. Political will, good governance, and sustainable financing are essential for successful implementation. The technical innovation aspect of the 100DM should prioritize the development of prototype vaccines and operational components over more long-term initiatives with broader impacts. To realize CEPI’s vision, global stakeholders must set priorities and commit to focused, coordinated actions. Achieving early wins through short-term, high-impact deliverables and actionable policy reforms is essential to build confidence, sustain momentum, and prevent stakeholder fatigue. This strategic prioritization underpins the initiative’s long-term success.